Vae Victis! Spatial Planning in the Rescaled Metropolitan Governance in France - Geppert, Anna (Raumforschung und Raumordnung | Spatial Research and Planning, 2017)
The paper focuses on the gap between the expectations and the effects of the recent rescaling of planning powers in France. Through a series of legislative reforms in 2010, 2014 and 2015, France has introduced “metropolises”. Designed for large cities of more than 500,000 inhabitants, metropolises are a new way of grouping municipalities (Etablissement Public de Coopération Intercommunale), more integrated than the previous bodies which they replace (communauté urbaine, communauté d’agglomération). With enlarged territories and increased decisional power, they were expected to become strong collective actors, providing better services for their inhabitants and making better use of their resources. However, the first outcomes of the reform do not meet these expectations. Metropolises are often smaller than expected. Their perimeters result more from political bargains than from geographical considerations. The emergence of a collective metropolitan power is slowed down by the mayors, who stick to localist approaches, as well as by the national government. Planning objectives have shifted from a redistributive approach (ensuring balanced territorial development) to a growth-oriented policy (enhancing metropolitan potentials). As a result, central areas are gaining economic weight and autonomy while peripheral areas keep declining: there are winners and losers.
Keywords: Spatial planning; Territorial reform; Metropolitan governance; Inter-municipal collaboration; Rescaling; France